2019
DOI: 10.1002/ijc.32680
|View full text |Cite
|
Sign up to set email alerts
|

Agnostic Cys34‐albumin adductomics and DNA methylation: Implication of N‐acetylcysteine in lung carcinogenesis years before diagnosis

Abstract: Although smoking and oxidative stress are known contributors to lung carcinogenesis, their mechanisms of action remain poorly understood. To shed light into these mechanisms, we applied a novel approach using Cys34-adductomics in a lung cancer nested case-control study (n = 212). Adductomics profiles were integrated with DNA-methylation data at established smoking-related CpG sites measured in the same individuals. Our analysis identified 42 Cys34-albumin adducts, of which 2 were significantly differentially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…In that study, the BDE adduct was detected in 8/10 of the exposed subjects, but not detected in any of the controls (levels in control participants were imputed with values of the lower limit of detection). This is in line with other studies using the DDA-based Cys 34 adductomics assay, in which the BDE adduct has not been detected in settings without high levels of benzene exposure. ,,,, While the BDE adduct may have been present in sera of subjects from these other reports, it only reached the threshold for DDA analysis in individuals with very high-benzene exposures (>3 ppm). In contrast, using our targeted PRM assay, we detected the BDE adduct in 77 of 78 samples (BDE was not detectable at the baseline in one subject), facilitating longitudinal biomonitoring of exposure to ambient levels of benzene (ppb) and exploration of BDE adduct as a dosimetric biomarker of OAP (+465%, +319%, and +376% per doubling of NO 2 , SO 2 , or PM 10 , respectively).…”
Section: Discussionsupporting
confidence: 90%
“…In that study, the BDE adduct was detected in 8/10 of the exposed subjects, but not detected in any of the controls (levels in control participants were imputed with values of the lower limit of detection). This is in line with other studies using the DDA-based Cys 34 adductomics assay, in which the BDE adduct has not been detected in settings without high levels of benzene exposure. ,,,, While the BDE adduct may have been present in sera of subjects from these other reports, it only reached the threshold for DDA analysis in individuals with very high-benzene exposures (>3 ppm). In contrast, using our targeted PRM assay, we detected the BDE adduct in 77 of 78 samples (BDE was not detectable at the baseline in one subject), facilitating longitudinal biomonitoring of exposure to ambient levels of benzene (ppb) and exploration of BDE adduct as a dosimetric biomarker of OAP (+465%, +319%, and +376% per doubling of NO 2 , SO 2 , or PM 10 , respectively).…”
Section: Discussionsupporting
confidence: 90%
“…29 In another study of occupational exposure to benzene, a positive association was found for putative benzene metabolite adducts. 30 Furthermore, the Cys34 method has been applied in studies of lung cancer 31 and childhood leukemia. 32 Adducts to the N-terminal amino acid valine in Hb can be analyzed after detachment with a modified Edman degradation.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the cysteine residue at position 34 (Cys34) of HSA is an effective target of cellular oxidation, generating a host of covalent modi cations to circulating thiols that act as redox switches in homeostatic processes (7b, 8). An untargeted adductomics approach has been developed and implemented in prior studies to identify Cys34 modi cations associated with exposure to environmental agents and certain chronic diseases, including cancers (6,(8)(9)(10)(11)(12). This approach, thus, has been proposed as a novel method to characterize exposure biomarkers and understand the etiology of oxidative stress-related diseases, including many cancers.…”
Section: Introductionmentioning
confidence: 99%